Age- and gender-related variations of cervical muscle composition using chemical shift encoding-based water-fat MRI. Issue 125 (April 2020) - Burian, Egon; Franz, Daniela; Greve, Tobias; Dieckmeyer, Michael; Holzapfel, Christina; Drabsch, Theresa; Sollmann, Nico; Probst, Monika; Kirschke, Jan S.; Rummeny, Ernst J.; Zimmer, Claus; Hauner, Hans; et al.
Highlights: Quantitative water-fat MRI is applied to determine cervical muscle fat alterations. Age- specific fat infiltration patterns of the paraspinal muscles are shown. Paraspinal fat fraction is elevated in women at the levels C3 and Th1 as compared to men. The presented data may serve as reference values for future detection of pathological processes. Abstract: Purpose: To understand fat distribution patterns and ectopic fat deposition in healthy adults and to provide normative data, encompassing the borders of physiological regional muscle composition. For this purpose chemical shift encoding-based water-fat Magnetic Resonance Imaging (MRI) was used for proton density fat fraction (PDFF) calculations. Material and methods: 91 volunteers were enrolled (male: n = 28, age = 36.6 ± 11.4 years; female: n = 63, age = 38.5 ± 15.1 years). PDFF values combined for the multifidus, semispinalis and spinalis cervicis muscles at the level of the 3rd cervical vertebral body (C3), the 5th cervical vertebral body (C5) and the first thoracic vertebral body (Th1) were extracted. Results: The paraspinal musculature at C3 (14.8 ± 10.1 % vs. 19.2 ± 11.0 %; p = 0.029) and Th1 (13.8 ± 7.0 % vs 17.7 ± 7.4 %; p = 0.011) showed significantly lower PDFF values in men compared to women. Partial correlation testing with BMI as control variable revealed highly significant correlations between the paraspinal musculature PDFF at C3 (men: r = 0.504, p = 0.007; women: r = 0.279, p = 0.028), C5 (men: r = 0.450, p = 0.019; women: r = 0.347, p = 0.006) and Th1 (men: r = 0.652, p < 0.0001; women: r = 0.443, p < 0.0001) with age in both genders. Conclusion: The present data suggest gender and age-specific fat deposition patterns of the cervical and the upper cervicothoracic paraspinal muscles and may provide reference values for pathology detection.